THE RELATIONSHIP BETWEEN MUROTTAL AL-QUR'AN ANDEFFLEURAGE MASSAGE USING JITU OIL BY BREAST MILK GRANDMOTHERS WITH INDEPENDENCE IN BREASTFEEDINGMOTHERS - Ningsih, Dewi Andariya; Rahayu, Sri; Sakinah, Innama (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2025)
The negative influence of grandmother's advice about breastfeeding is related to wrong knowledge and not intentional. When they have adequate information, grandmothers' roles in feeding their grandchildren will be vulnerable and changeable, resulting in better feeding patterns. During the postpartum period, grandmothers can also pass on to their children information that is very useful for daughters/daughters-in-law, some of which can also hinder breastfeeding. In this research, we will examine the effect of Al-Qur'an murottal and Effleurage massage using Jitu Oil on breastfeeding independence in mothers assisted by breastfeeding grandmothers. Postpartum mothers who are giving birth for the first time will be confused about what steps need to be taken to meet the baby's nutritional needs, so the role of those closest to them, especially grandmothers, is needed in ensuring this is achieved.This research uses a quasi-experimental design using a one test only design. The working area of ​​the Arjasa Community Health Center, Situbondo Regency, was used as the location for this research. The research was carried out from December 2023 to February 2024. The research population was postpartum mothers in the TPMB working area of ​​the Arjasa Health Center using purposive samplingas many as 41 people. The resultsMothers who breastfeed independently tend to have a chance of having confidence in breastfeeding which is 3.167x higher than mothers who have low breastfeeding independence.